Realita dan Akuntansi: Kasus Penelitian Akuntansi Dengan Pendekatan Interpretive - Yudhanta Sambharakreshna (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
Economic reality plays an important role in accounting practice and standard setting process. The positivism paradigm view reality as independently existing, and interpretive paradigm view reality as socially constructed. It is argued in this paper that utilizing interpretive view in accounting research is better able to capture the economic reality that is socially constructed and much affected by our account. This is because accounting is a social science and is better understood by gaining the views of different parties involved, which is largely done by utilizing interpretive accounting research.